The Effectiveness of Problem Based Learning Integrated With Islamic Values Based on ICT on Higher Order Thinking Skill and Studentsâ Character - Anwar, Chairul (Institut Agama Islam Negeri Imam Bonjol Padang, 2016)
The focus of this research is to known the influence of Problem Based Learning (PBL) model application, that intergrated with Islamic values based on ICT, toward the ability of higher-order thinkingskill and the strenghtening of studentsâ characters. This research is quasy experiment type with group design pretest-postest. The research was conducted in SMA.Sampling by means of random sampling, to determine the control class and experimentalclass.Data analysis technique used is the t-test, based on the value of significance, as well as test-effect size. The research data shows that the model of problem based learning integrates Islamic values based on ICThas positive influence towards the increasing of higher-order thinking skill and the strenghtening of studentsâ characters compared to the students that use conventional method.The result of effect size test on experimental class in on medium category. It means that the learning which use problem based learning (PBL) model, integrated with Islamic values based on ICT, can be said effective on increasing higher order thinking skillof students.